Revenue Management Performance Drivers: An Empirical Analysis at Four Points by Sheraton - Shroff, Avinash (2009)
The purpose of this management project is to analyse the current and future scenario of the revenue streams of the Four Points hotel Mumbai in India. Revenue Management (RM) is an important tool for matching supply and demand by segmenting customers into different segments based on their willingness-to-pay and allocating scarce capacity to the different segments in a way that maximizes firm revenues. The benefits of RM are well accepted in the hospitality industry, and the technical aspects of RM form a rich analytical research stream. Forecasting for a hotel revenue management system is intrinsically difficult. Competitive actions, seasonal factors, the economic environment and regular fare changes are but a few of the challenges that must be overcome. This report examines the challenge of forecasting for Four Points hotel’s revenue management system being a fairly new hotel in Mumbai. With the Indian economy booming, India is increasingly becoming a centre for tourists and business destination. This report aims to study the trends in the hospitality industry and analyse the current situation of Four Points hotel Mumbai’s various revenue management models to enable the hotel to increase sales to enhance its business performance and create its own identity in the world of Hospitality. Mice tourism, pricing, and various concepts of revenue management are few others covered in this report. The literature shows that market segmentation, pricing, forecasting, capacity allocation, contribute to effective RM. In this report these elements have been grouped into two concepts: RM technical capability and RM social support capability and propose that these four elements positively impact RM performance. The number of rooms a hotel can sell and at what price is all determined by the booking limits set by the revenue management system. Standard rooms are the lowest category of rooms available which are always overbooked. The hotels continue to sell these rooms until the booking limit is reached after which the hotel does not show vacancy on those categories. Demand in that class of rooms may exceed the booking limit, but the data does not reflect and this is censored or “constrained” at the booking limit.